Development of mild encephalitis with a reversible splenial lesion prior to the diagnosis of Kawasaki disease: a pediatric case report - Yamanouchi, Hirokazu; Onoyama, Sagano; Marutani, Kentaro; Harada, Nobutaka; Ueno, Yuji; Kanemasa, Hikaru; Kira, Ryutaro; Kaneko, Shuya; Shimizu, Masaki; Hoshina, Takayuki (Frontiers in Pediatrics, 2025)
Kawasaki disease (KD) rarely causes neurological complications. KD is diagnosed based on symptoms alone and can be very difficult to diagnose if other symptoms appear in febrile children before the main symptoms of KD. A 5-year-old boy with fever and consciousness disturbance was hospitalized and diagnosed with mild encephalitis/encephalopathy with reversible splenial lesion (MERS). The fever and consciousness disturbance resolved with intravenous methylprednisolone for 3 days (30 mg/kg/day) and intravenous immunoglobulin (IVIG; 1 g/kg/day) for 2 days, which was initiated as treatment for MERS. However, bilateral conjunctival injections, redness of the lips, and membranous desquamation of the fingers were observed, followed by recurrence of fever four days after the initial treatment. Echocardiography revealed dilation of the right coronary artery (RCA). The patient was diagnosed with incomplete KD and was treated with high-dose IVIG and oral aspirin based on the presence of four major KD symptoms and coronary artery dilation. After treatment, he showed defervescence, and the RCA showed no further dilation on echocardiography. Clinicians should recognize that the development of MERS may precede the diagnosis of KD in some patients. In addition, patients with MERS of unknown etiology, leukocytosis, and elevated serum CRP levels should be closely monitored because of the possibility of KD.